A thermodynamic model of sliding friction - Lasse Makkonen (AIP Advances, 2012)
A first principles thermodynamic model of sliding friction is derived. The model predictions are in agreement with the observed friction laws both in macro- and nanoscale. When applied to calculating the friction coefficient the model provides a quantitative agreement with recent atomic force microscopy measurements on a number of materials.